Seasonally driven internal P and N nutrient (re)cycling strategies of beech saplings are element specific - Herschbach, Cornelia; Samuilov, Sladjana; Kalio, Magdalena Klara; Schramm, Christoph; Krüger, Jaane; Löw, Caroline Anna Elisabeth; Büttner, Michael; Lang, Friederike (Environmental and experimental botany, 2022)
Excessive N deposition leads to the conversion of previously N limited to N saturated forest ecosystems. The input of N can result in severe N/P imbalance and N-induced P deficiency. The present study investigates whether N addition induces P deficiency in beech saplings or if this can be counteracted by enhanced internal P (re)cycling. Furthermore, it was tested whether addition of P can mitigate N induced P deficiency. In addition, higher need of P due to enhanced growth may be realized either by enhanced P uptake or by improved internal P (re)cycling. This assumption was tested with beech saplings growing at higher light intensity. Therefore, a mesocosm approach with beech saplings and soil (O and A horizon) originating from a P-poor forest was conducted. Mesocosms were cultivated for two growing seasons in a garden. Addition of N, P, or combined addition of N and P took place during the first year and another group of saplings was exposed to higher light intensity to enhance CO2 assimilation and growth. Soil horizons and beech saplings were harvested during the second year of growth in spring, summer, autumn, and winter. The results show that internal (re)cycling of N and P is different and mostly determined by the season. The seasonal (re)cycling of P was driven by the metabolic P demand of tissues/organs characterized by shifting P between the perennial tissues bark and wood of branches and coarse roots and deciduous leaves, fine roots and long-distance transport paths without using major storage resources. In contrast, seasonal (re)cycling of N is characterized by N storage in perennial tissues during dormancy and by N mobilization from the entire trunk, i.e. branch, stem and coarse roots, in spring. Furthermore, these seasonal dynamics were found to be independent of the treatment.